Marguerite Mespoulet et Madeleine Mignon en Irlande pour les Archives de la Planète : influences hors champ - Karine Bigand (Revue LISA)
The seventy-three autochromes that Marguerite Mespoulet and Madeleine Mignon took in Ireland and May and June 1913 were the first colour photographs of the island. They show traditional habitat, costumes, bog landscapes and crafts, as well as famous Celtic and early Christian monuments. However, far from being a holiday album or a tourist photocall, the two travellers’ Carnet d’Irlande forms part of a specific ideological and scientific project, designed and sponsored by banker Albert Kahn. The Archives de la Planète project, launched in 1912, was to draw “a form of photographic inventory of the surface of the Earth, as it is occupied and managed by men at the beginning of the 20th century1.” The mission to Ireland was one of the first to be carried out, by two experienced travellers and confirmed intellectuals, Marguerite Mespoulet and Madeleine Mignon. This paper explores how and to what extent their view of Ireland at the turn of the century was informed by the ideological, methodological and technical constraints they had to respect.